Molecular Diagnostics for Monitoring Insecticide Resistance in Lepidopteran Pests - Camila Ivo C. Vilarinho Fernandes Junqueira; Eliza F. de Melo Bellard do Nascimento; Leonardo A. Vidal; Erick S. Lustosa de Queiroz; Erika V. Saliba Albuquerque (Agronomy)
Chemical control methods to prevent crop damage have long been directly implicated in the selection of lepidoptera insect populations resistant to insecticides. More recently, new products featuring different modes of action (MoA), developed to mitigate the negative effects of control management on both producers and the environment, are rapidly losing efficacy due to the emergence of resistant insects. Among these, certain resistances are associated with molecular changes in the genomes of pest insects that are valuable for developing molecular markers for diagnostic tools, particularly the point mutations. Molecular diagnosis represents an innovative solution for insecticide resistance management (IRM) practices, allowing for the effective monitoring of insecticide resistance. This approach facilitates decision making by enabling the timely alternation between different modes of action (MoAs). In this context, this review focuses on the major lepidopteran pests that affect globally significant crops, discussing the impacts of insecticide resistance. It gathers literature on diagnostic methods; provides a comparative overview of the advantages of different techniques in terms of efficiency, cost, precision, sensitivity, and applicability; and highlights several novel diagnostic tools. Additionally, this review explores the coffee leaf miner, Leucoptera coffeella, as an applied model to illustrate potential approaches for more effective and sustainable control strategies.